Reduction in advanced breast cancer after introduction of a mammography screening program in Tyrol/Austria. (June 2017) - Oberaigner, W.; Geiger-Gritsch, Sabine; Edlinger, M.; Daniaux, M.; Knapp, R.; Hubalek, M.; Siebert, U.; Marth, C.; Buchberger, W.
Abstract: Background: We analysed all female breast cancer (BC) cases in Tyrol/Austria regarding the shift in cancer characteristics, especially the shift in advanced BC, for the group exposed to screening as compared to the group unexposed to screening. Methods: The analysis was based on all BC cases diagnosed in women aged 40–69 years, resident in Tyrol, and diagnosed between 2009 and 2013. The data were linked to the Tyrolean mammography screening programme database to classify BC cases as "exposed to screening" or "unexposed to screening". Age-adjusted relative risks (RR) were estimated by relating the exposed to the unexposed group. Results: In a total of about 145, 000 women aged 40–69 years living in Tyrol during the study period, 1475 invasive BC cases were registered. We estimated an age-adjusted relative risk (RR) for tumour size ≥ 21 mm of 0.72 (95% confidence interval (CI) 0.60 to 0.86), for metastatic BC of 0.27 (95% CI 0.17 to 0.46) and for advanced BC of 0.83 (95% CI 0.71 to 0.96), each comparing those exposed to those unexposed to screening, respectively. Conclusion: In our population-based registry analysis we observed that participation in the mammography screening programme in Tyrol is associated with a 28% decrease in risk for BC cases with tumour size ≥ 21 mm and a 17% decrease in risk for advanced BC. We therefore expect the Tyrolean mammography programme to show a reduction in BC mortality. Highlights: We categorized all breast cancer cases diagnosed in Tyrol/Austria as "exposed to screening" and "unexposed to screening". We estimated a relative risk for advanced breast cancer of 0.83 (95% CI 0.71 to 0.96) for those exposed to screening. This important surrogate measure leads us to expect the Tyrolean mammography program to show a reduction in BC mortality.